EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN MANGGIS DAN POTENSI PENGEMBANGANNYA DI KECAMATAN PAUH KOTA PADANG - Dyah Puspita Sari; Ranti Novia; J Juniarti (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Pauh District was chosen as mangosteen plantation development centre in Padang City. This development should be based on the land suitability so that the mangosteen plant are able to grow according to the climate and soil conditions. This research was conducted in Pauh District, Padang City and Soil Science Laboratory Andalas University. This study used a survey method that consisted of preparation, pre-survey, the main surveiy, laboratory analysis, and data processing. Evaluation of land suitability was done with matching method which compare the characteristics of land suitability for mangosteen growth. The results of research showed that land suitability for mangosteen was classified into S3 (marginally suitable) with subclass S3nr for land unit SL1, SL2, SL3, SL4, SL7, SL8, SL9, SL11, SL15; subclass S3eh for land unit SL14; subclass S3nr,eh for land unit SL5 and SL10. Land unit SL6, SL12, SL13, and SL16 were classified into S2 (moderately suitable) with subclass S2wa,nr for land unit SL6 and SL16; subclass S2wa,rc,nr,eh for land unit SL12; subclass S2wa,rc,nr for land unit SL13. The limiting factors was common to each land unit were nutrient retention (nr) and erosion (eh). There are 3 villages (Lambung Bukit, Limau Manis, and South Limau Manis) in Pauh District which have the greatest potential to be developed as mangosteen plantation development areas with total area was 5,862.42 ha.